2010
DOI: 10.1007/s11434-009-0501-z
|View full text |Cite
|
Sign up to set email alerts
|

Flame instability analysis of diethyl ether-air premixed mixtures at elevated pressures

Abstract: Combustion characteristics of premixed diethyl ether-air mixtures were studied at different equivalence ratios and elevated initial pressures using schlieren photography and spherically propagating flame. Laminar burning velocities, Markstein number and critical radii at onset of cellular structure were obtained. The results show that an increase in initial pressure leads to a decrease in the unstretched laminar burning velocities. Laminar burning velocities give their peak values at the equivalence ratio of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…There has been much work recently on the combustion characteristics of DEE, but none that has impinged on the chemical kinetics of this system. In the present work, we have carried out pyrolysis and oxidation experiments behind reflected shock waves and constructed a detailed chemical reaction model to describe these.…”
Section: Introductionmentioning
confidence: 99%
“…There has been much work recently on the combustion characteristics of DEE, but none that has impinged on the chemical kinetics of this system. In the present work, we have carried out pyrolysis and oxidation experiments behind reflected shock waves and constructed a detailed chemical reaction model to describe these.…”
Section: Introductionmentioning
confidence: 99%
“…Burning velocities of DEE have been measured by Gibbs and Calcote [23] using a Bunsen burner flame cone and the apex-cone method. Di et al [24] and Zhang et al [25,26] used a spherically propagating flame in a cylindrical vessel to obtain laminar burning velocities and study the combustion characteristics of diethyl ether. However no results have been reported for DEE flame velocities using the heat flux method.…”
Section: Introductionmentioning
confidence: 99%
“…This includes IDTs measured in RCMs and shock tubes 67,[70][71][72][73] ; speciation measurements collected from JSR, plug flow reactor (PFR), and shock tube experiments 10,[74][75][76][77][78] ; and several studies of DEE flames. [79][80][81][82][83][84] In parallel to this experimental exploration of DEE combustion, several studies have attempted to produce detailed kinetic models to predict the observed behavior.…”
Section: Diethyl Ethermentioning
confidence: 99%